A Study on the Use of Orifice Plates as Steam Traps - Sulaiman, S. A.; Jamaludin, S. E. (2010)
Steam traps are vital part in most steam systems in order to prevent the passage of the hot vapor while allowing water condensate to flow. A conventional steam trap is simply a self-actuating valve that opens in the presence of condensate and closes in the presence of steam. These traps all have moving parts, which, in time will fail. Another non-conventional type of steam trap is known as orifice plate steam trap. The design consist a plate with small hole at the middle to allow condensate to pass through it. The trap uses the condensate within its orifice to hold back steam, rather than any valve arrangement. Orifice plate steam traps have no moving parts that can malfunction, and thus it has minimal problems that are related to mechanical failure. Under certain circumstances, orifice steam traps could function better than the conventional traps. However the performance of orifice plate steam traps is not well understood. The purpose of this paper is to compare the effectiveness of fixed orifice plate steam traps over variable loads. This is achieved by conducting experiments that measure the rate of steam loss under different condensate loads. It is found that fixed orifice plates are only suitable for a steam system with constant condensate load.